Pelatihan Pembuatan Asesmen Pembelajaran Berbasis Kuis Interaktif Bagi Guru Matematika di SMA Pertiwi 1 Padang - Mulia Suryani; Melisa Melisa; Rahmi Rahmi (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
The independent learning curriculum requires teachers to innovate by utilizing technology. Therefore, teacher skills are needed in using technology, not only in delivering material but also in designing learning assessments. However, the teacher's knowledge at SMA Pertiwi 1 Padang in designing electronic-based learning assessments is still very limited. As a manifestation of Higher Education's Tri Dharma, community service activities are carried out in the form of training, with the title "Training in Making Interactive Quiz-Based Learning Assessments for Mathematics Teachers at SMA Pertiwi 1 Padang". The aim of the training is for teachers to: 1) familiar with the IT-based evaluation system, 2) teacher able to compose questions using an IT-based assessment model in the form of interactive quizzes independently; 3) teacher able to apply the evaluation system in learning. The application used in making the assessment is Kahoot. The method applied in this training is the Participatory Rural Appraisal (PRA) method. After the training activities the team gave a questionnaire to see the achievement of the objectives of the training activities. This training data analysis uses percentage calculations. Based on the results of the analysis of the implementation of training activities, it was concluded that 1) The teacher's skills in using ka-hoot to make learning evaluation instruments increased, 2) Teachers better understood the importance of making online evaluation instruments, 3) These training activities could improve skills, creativity and the quality of learning evaluation.